Optical rectification by ratchet transport in an asymmetric grating - P. Moroshkin; T. Ochiai; R. Osgood III; J. Xu (AIP Advances, 2021)
We report on electron ratchet transport’s manifestation in the optical rectification (OR) of an asymmetric grating. The photon-drag enabled effect is magnified by asymmetric photon scatterings and the induced optical nonlinearity associated with the surface plasmon polariton (SPP) via its near-field and gradient intensifications. The measured OR efficiency is increased multi-fold, over the prior art, which is attributable to its operating in a higher-order diffraction and nonlinearity regime and to a minimized coupling loss to a potential SPP mode at the lower interface.